The Marine Protection Regime in Svalbard’s maritime zones with regard to Cruise Tourism - Skrøland, Henriette Nicolaysen (UiT Norges arktiske universitet, 2016)
The goal of this thesis was to present and analyze the international and national regimes governing marine environmental protection and tourism in the waters of Svalbard. Three questions where addressed: 1) What international and national legislation is applicable to Svalbard with regard to marine environmental protection and tourism? 2) What international and national legislation is applicable to ship-based pollution in the waters of Svalbard? and 3) Does Norway have enforcement jurisdiction in the case of tourism activities and ship-based pollution in the waters of Svalbard? There is a complex legal regime in place in the Arctic and Svalbard. On the international level, the LOSC, the IMO instruments SOLAS and MARPOL 73/78 and the London Convention are the main conventions and organizations that gives the framework and jurisdiction related to ship-based pollution on Svalbard. The WWF International Arctic Programme has also been central in the research and discussion related to cruise tourism in Svalbard, as it has done research and gives a great overview over cruise tourism in the Arctic. There is some controversy regarding the applicability of the Svalbard Treaty in the Continental Shelf and the FPZ. Until this issue is solved, there will be some challenges associated with legislation and enforcement. If some of the ships flying the flag of another state do not agree with Norway’s enforcement jurisdiction and competence to implement regulations in the waters of Svalbard, conflicts can arise. Furthermore, as interests in oil, gas and tourism increases, the more controversy there are in these areas, the chances of conflicts will likely increase as well. At the national level, there are several laws and regulations that deals with marine environmental protection and tourism in Svalbard. Among these are the Svalbard Treaty, the Svalbard Act, SEPA and the regulations relating to tourism, field operations and other travel. These laws and regulations contains important provisions to protect one of the last wilderness ...